High-dimensional mediation analysis in survival models - Luo, Chengwen; Fa, Botao; Yan, Yuting; Wang, Yang; Zhou, Yiwang; Zhang, Yue; Yu, Zhangsheng (PLOS Computational Biology, 2020)
Author summary In this research, we established an efficient procedure for high-dimensional mediation analysis with time-to-event data to select DNA methylation markers and estimate the mediation effects. To evaluate the performance of the proposed procedure, we conducted extensive simulation studies and analyzed a lung cancer data set using our method. We demonstrated the validity and utility of our method under a variety of scenarios.